Restoration of natural killer cell activity by pegylated interferon‐alpha/ribavirin therapy in chronic hepatitis C patient. Issue 1 (24th April 2014) - Nakamura, Ikuo; Asano, Takeharu; Asabe, Shinichi; Ando, Mayumi; Sano, Takatomo; Miyata, Yuki; Taira, Junichi; Sugimoto, Katsutoshi; Imai, Yasuharu; Moriyasu, Fuminori; Imawari, Michio
<x xml:space="preserve">Abstract</x> Aim The combination therapy of pegylated interferon‐α and ribavirin (PEG IFN/RBV) is one of the effective treatments for chronic hepatitis C (CHC) patients. Natural killer (NK)‐cell activity was reported to be impaired in patients with hepatitis C virus (HCV). The aim of this study was to examine whether PEG IFN/RBV therapy could restore NK activity in CHC patients. Methods In 19 CHC patients, PEG IFN/RBV therapy was performed. Just before (0M), at 3 months of the therapy (3M) and at 6 months after completion of the therapy (6M), NK activity and the frequency of NK cells, CD56dimNK cells and CD56brightNK cells in peripheral blood was estimated by creatinine release assay and flow cytometry. Statistical analysis was performed by anova and Mann–Whitney U‐test. Results anova showed that NK activity significantly improved at 6M (vs 0M, P < 0.05) in the patients studied and in the patients with sustained virological response (SVR). It also showed that frequency of CD56brightNK cells was significantly increased at 6M (vs 0M, P < 0.05) in the patients studied and in the SVR group. However, no significant change in NK activity and frequency of CD56brightNK cells were detected in non‐SVR group. Furthermore, NK activity ratio (6M/0M) in the SVR group was revealed to be higher compared with that in the non‐SVR group by analysis using Mann–Whitney U‐test (P < 0.05). Conclusion PEG IFN/RBV therapy in CHC patients could improve NK activity by increasing the frequency of CD56brightNK cells in SVR patients. Our study also revealed that eradication of HCV could restore NK‐cell activity.